Observation of the Auto Tracking Process of 5 KWP PLTS at HKBP Nommensen University - Timbang Pangaribuan; Fiktor Sihombing; Reinhard Sitinjak (Golden Ratio of Data in Summary, 2026)
HKBP Nommensen University in 2022 received a Kedaireka Matching Fund-2022 Grant, and the research was carried out to build 3 PLTS units at UHN Medan, namely 10 KWP, 5 KWP and 2 KWP, with the title Prototype Autotracking PLTS UHN Medan. The research with the grant has been successfully implemented and has served UHN's electricity night lighting. The follow-up to the research is to provide opportunities for Lecturers and Students to conduct independent campus research internships for students of the Electrical Engineering Study Program and other study programs that require it. This research has joined student research conducted by special research by research lecturers with a lecturer and a student, with the title Observation of the Autotracking Process of 5 KWP PLTS at UHN Medan. This research was carried out together with the lecturer and the student. The autotracking observation aims to see several things including, can the autotracking movement reach a vertical position to sunlight? Next, the effect of autotracking on increasing the efficiency of the 5 KWP PLTS will be observed. The output of this research is planned to be in the form of a journal. From the observations, research data will be obtained for further analysis.